The state of art in the horticulture lighting - Gilewski, Marian (Photonics Letters of Poland, 2020)
The article presents an overview of currently used greenhouse lighting systems. It does not apply to traditional sodium lighting systems, but only to the most modern LEDs. The publication presents descriptions of lamp designs, both foreign and Polish. The aim of the work is not only to review solutions, but also to identify the reasons for the low transfer of scientific and technical solutions to business. There are several barriers to overcome, mainly subjective ones, so that new solutions can be implemented and developed. Full Text: PDF References S. Ki-Ho, J. Yu-Min, O. Myung-Min, "Application of supplementary white and pulsed light-emitting diodes to lettuce grown in a plant factory with artificial lighting", Springer 57(6), 561 (2016). CrossRef M. Gilewski, "The role of light in the plants world", Phot. Lett. Poland 11, 4 (2019). CrossRef K.J. McCree, Agricultural Meteorology (Elsevier Publishing Company 1972). CrossRef G. Trouwborst, J. Oosterkamp, S. Hogewoning, V. Ieperen, "The application of LEDs as assimilation light source in greenhouse horticulture: A simulation study", the 6th Int. Symposium on Light in Horticulture. Tsukuba. Japan, Nov. 2009. CrossRef K. Jaworski, A. Szmidt-Jaworska, J. Kopcewicz, " Two calcium dependent protein kinases are differently regulated by light and have different activity patterns during seedling growth in Pharbitis nil", Springerlink.com, Journal: 10725, Article: 9609, 2011. CrossRef Philips Lighting, Horticultural LED lighting applications, 2020: https://www.lighting.philips.com/main/products/horticulture. DirectLink E. de Beer, P.H. van Baar, 3 reasons why intercanopy lighting is effective for high-wire vegetables, 2020: www.lighting.philips.com. DirectLink HLG, Refurbished HLG 550, 2020, https://horticulture-lightinggroup.com/collections/lamps/products/refurbished-hlg-550-v1 DirectLink Neonica Polska, 2020, www.growy.eu CrossRef I. Fryc, T. Dimitrova-Grekow, "An automated system for evaluation of the quality of light sources", 6th IEEE Lighting Conference of the Visegrad Countries : LUMEN V4, Sept. 2016. CrossRef EconoLux Ind. Ltd., "What Light do Plants Need", Hong Kong, 2016, http://econoluxindustries.com/light-plants-need.html. DirectLink Heliospectra AB, heliospectra DYNA, 2020, https://www.heliospectra.com/led-grow-lights/dyna. DirectLink Plantlux, Horticulture LED SMD lamp Plantalux XX640W, 2020, https://plantalux.pl/en/plantalux-xx640w-en/. DirectLink M. Gilewski, "An Adaptive and Monoculture Oriented LEDs Lamp", 978-1-5386-7924-1/18/31.00 ©2018 IEEE, 2018. CrossRef